POLA MAKAN DAN ASUPAN NATRIUM PADA LANSIA HIPERTENI DI WILAYAH KERJA PUSKESMAS TARERAN - Daniel Robert; Irza N. Ranti; Stefani C. Karundeng (Jurnal GIZIDO, 2015)
Hypertension or high blood pressure is one health problem that is dominant and needs tobe addressed, because the prevalence rate is high and also due to long-term damagecaused has certain consequences. Hypertension often has no signs or symptoms, or oftencalled the "silent killer" or a disease that kills secretly or covertly. Society is not aware thatthey have hypertension until a strain on the heart, brain or kidneys. Patients withhypertension in the world close to 1 billion. That is, 1 in 4 adults suffer from high bloodpressure. More than half, or about 600 million people, scattered in developing countries,including Indonesia State. The aim of research to determine the Diet (type, frekuensu,number) and Sodium Intake in the Elderly Hypertension in Puskesmas Tareran.This research is descriptive research with survey method. The number of respondents 44people aged> 65 years, suffering from hypertension and willing to become respondents.The results of the 44 respondents, type of food consumed is food that can lead to highblood pressure (hypertension) such as: meat (pork, beef, duck, chicken), offal, brains,squid, shrimp, anchovies, clams, crabs , salted eggs, shellfish, crab, salted egg, salt, MSG,alcohol, soft drinks (Fanta). Frequency of eating respondents to the type of foodmengkibatkan hypertension is 2-3 times / week and 2-3kali / bulanJumlah consumption ofrespondents to the type of food that can be mengkibatkan hypertension is 71-75 grams ameal. Average sodium intake of respondents is 742 mg / day.